Diagnostic concordance of phyllodes tumour of the breast. Issue 4 (21st June 2021) - Rakha, Emad; Mihai, Raluca; Abbas, Areeg; Bennett, Rachel; Campora, Michela; Morena, Philippa; Toss, Michael; Ellis, Ian
Abstract : Aims: Phyllodes tumours (PT) are rare and distinct breast tumours, which span a morphological continuum. Classification into benign, borderline and malignant categories reflects their biology and clinical behaviour and is essential to guide management. This study aims to assess the diagnostic agreement of PT using the UK National Health Service Breast Screening Programme (NHSBSP) breast pathology external quality assurance (EQA) scheme data. Methods and results: Twenty‐six PTs were identified in the EQA scheme, which were diagnosed by an average of 607 participants/circulation. Data on diagnostic categories were collected and representative slides were reviewed. The level of concordance between reporting pathologists was assessed. There were 14 benign, six borderline and six malignant PT. The overall rate of diagnosis agreement was 86% when analysed as benign lesions, borderline PT and malignant lesions, which decreased to 79% when diagnosed as PT (irrespective of grade) and to 63% when the diagnosis was further refined to PT categories (benign, borderline and malignant PTs). The highest agreement rate was observed in malignant PT (86%) and the lowest in borderline PT (42%). Malignant heterologous elements, stromal overgrowth and leaf‐like architecture are features associated with higher concordance rates. Lower‐priority features were stromal expansion, clefting and multinodularity. Conclusion: The concordance of PT diagnosis, as an entity, is high, but its classification into benign, borderline and malignant has variable agreement levels, with borderline tumours having the lowest concordance rate. More research to refine the diagnostic criteria for categorisation of PT is warranted to improve concordance between pathologists. Abstract :